The influence of roughness on the resistance to impact of different CAD/CAM dental ceramics - Guilardi,Luis Felipe (2021)
Abstract This study aimed to investigate the effect of surface roughness (polished vs. CAD/CAM milling simulation) on impact strength of five dental ceramics for manufacturing CAD/CAM monolithic restorations. Specimens of five ceramics (FC- feldspathic glass-ceramic; PICN- polymer-infiltrated ceramic-network; ZLS- zirconia-reinforced lithium silicate glass-ceramic; LD- lithium disilicate glass-ceramic; YZ- yttria-stabilized tetragonal zirconia polycrystal ceramic) to be tested under impact (15×10×2mm3; n= 15) were divided into two groups, according to surface treatment: polishing (pol) and grinding (gri) as CAD/CAM milling simulation. Impact strength was tested using the Dynstat method. Roughness, topographic, fractographic and finite element analyses were performed. The impact strength data were analyzed by Weibull, and Pearson correlation was used to correlate roughness and impact strength data. The CAD/CAM milling simulation led to significantly (p<0.05) greater roughness (Ra and Rz) and statistically reduced the impact strength for PICN (polPICN= 4.59 to griPICN= 1.09; ±76% decrease), for LD (polLD= 17.69 to griLD= 10.09; ±43% decrease) and for YZ (polYZ= 74.99 to griYZ= 20.67; ±72% decrease) ceramics; and also promoted a more irregular topography with scratches and grooves. Fractographic and FEA analyses depicted the origin of failure at the higher stress concentration side during the impact test, where the pendulum impacted. The CAD/CAM milling simulation significantly decreased the impact strength of the evaluated ceramic materials.